2020
DOI: 10.1136/heartjnl-2020-316889
|View full text |Cite
|
Sign up to set email alerts
|

Association between right ventricle dysfunction and poor outcome in patients with septic shock

Abstract: ObjectiveSepsis-induced myocardial dysfunction (SIMD) can involve both the left and right ventricles. However, the characteristics and outcomes across various manifestations of SIMD remain unknown.MethodsThis was a retrospective cohort study using a prospective registry of septic shock from January 2011 and April 2017. Patients with clinically presumed cardiac dysfunction underwent echocardiography within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 30 publications
1
33
0
2
Order By: Relevance
“…Moreover, the 28-day mortality of SIMD patients was also elevated as compared to the NSIMD subjects; although this difference was not significant, it might be related to the small sample size. These discoveries were in line with previous studies, suggesting that the myocardial dysfunction will worsen the prognosis of sepsis or septic patients ( Frencken et al., 2018 ; Kim et al., 2020 ). According to this finding, we should pay more attention to the frequent complications of sepsis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the 28-day mortality of SIMD patients was also elevated as compared to the NSIMD subjects; although this difference was not significant, it might be related to the small sample size. These discoveries were in line with previous studies, suggesting that the myocardial dysfunction will worsen the prognosis of sepsis or septic patients ( Frencken et al., 2018 ; Kim et al., 2020 ). According to this finding, we should pay more attention to the frequent complications of sepsis.…”
Section: Discussionsupporting
confidence: 91%
“…SIMD was diagnosed established by both hs-cTnI levels and bedside transthoracic echocardiography (TTE). Specifically, hs-cTnI levels were monitored, and TTE was performed in the first 24 h of admission to ICU and if the parameter is higher than 0.04 ng/ml ( Kim et al., 2020 ) (a cutoff value that represents the 99th percentile reported in the healthy population). Meanwhile, an echocardiogram confirmed that the left ventricular ejection fraction (LVEF) <50% and/or ≥10% in the patient’s initial EF assessed on admission ( Jeong et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…RV dysfunction is common in severe sepsis/septic shock. Its prevalence ranges from 40% to 60% at admission but significantly increase when the enrollment lasts up to 72 h. RV dysfunction correlated with longer stay in ICU, and independently associated with higher risk of both early and long-term mortality [ 96 , 97 , 98 ]. Nevertheless, conflicting results exist and the complex geometry of RV—alongside the tight ventricular interdependence—raises many questions.…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…Most studies detected myocardial dysfunction with echocardiography, and one did so with afterload-related cardiac performance [ 19 ]. Among the studies using an echocardiogram, 17 defined SIC with LV dysfunction [ 8 , 10 , 20 25 , 27 32 , 34 , 35 , 38 ], and seven included RV dysfunction as well [ 18 , 22 , 26 , 33 , 36 38 ], Among the 17 LV dysfunction studies, 15 showed LVSD, and 12 of them defined abnormal LVSD as LVEF < 50%. One study described LVSD as pre-ejection period and LV ejection time ratio greater than 42% [ 21 ], and another presented LVSD with the ratio of fractional area change smaller than 50% [ 10 ].…”
Section: Resultsmentioning
confidence: 99%